FIRST REPORTED CASE OF MAJEED SYNDROME FROM PAKISTAN: Majeed Syndrome - Malik, Qudrat Ullah; Rahman, Asbah; Ikram, Farooq; Shoaib, Muhammad; Akhlaque, Uzma; Khalil, Muhammad Tawab (Pakistan Armed Forces Medical Journal, 2021)
Majeed syndrome, characterized by chronic recurrent multifocal osteomyelitis and congenital dyserythropoeitic anemia, is a rare disease reported in children. We report a case of Majeed Syndrome in a 9-year-old boy, born of consanguineous marriage reporting to us for treatment of anemia, requiring blood transfusion. He underwent below-knee-amputation due to unresolving recurrent osteomyelitis at multiple sites. There was history of pain insensitivity and fever during hot weather as well. His interleukin-6 levels were raised. This is the first case of Majeed Syndrome from Pakistan and first in the world with Hereditary Sensory Autonomic Neuropathy type 4 as an associated feature.